Kaloré Wue Goka, Goka Lodo Liku Puke: Menafsir Falsafah Kampung Keloreama Dan Pesan Didaktis Bagi Penduduk - Yosef Masan Toron (STIPAS St. Sirilus Ruteng, 2018)
This paper specifically speaks of the philosophy that lives in the kampong of Kelorema-Lamaholot and its didactic and contextual message for the living society today. With this theme, the author actually wants to invite people to love the depths of their own traditions since the movement to return to the root (back to basic) become a strategic breakthrough to counteract the negative impacts of modern progress. “Back to basic ” movement is not a step backward, but a powerful strategy for self-building and stewardship on the basis of local virtues to confront the negative effects of modern progress. A small study of the philosophy of Keloreama village is not merely a string of empty words, but it is a precious pearl that has a million worth of meaningful values of life. Effort to deepen the slogan of the village can be an entrance to uncover various values in local tradition and make it a solid pedestal for life in modern times.